UDP-N-acetyl-α-D-galactosamine:polypeptide N-acetylgalactosaminyl-transferase from the snail Biomphalaria glabrata – substrate specificity and preference of glycosylation sites - Taus, Christopher (Glycoconj J, 2014)
O-glycosylation is a widely occurring posttranslational modification of proteins. The glycosylation status of a specific site may influence the location, activity and function of a protein. The initiating enzyme of mucin-type O-glycosylation is UDP-GalNAc:polypeptide GalNAc transferase (ppGalNAcT; EC 2.4.1.41). Using electron-transfer dissociation mass spectrometry, ppGalNAcT from the snail Biomphalaria glabrata was characterized regarding its ability to glycosylate threonine and serine residues in different peptide sequence environments. The preferences of the snail enzyme for flanking amino acids of the potential glycosylation site were very similar to vertebrate and insect members of the family. Acceptor sites with adjacent proline residues were highly preferred, while other residues caused less pronounced effects. No specific O-glycosylation consensus sequence was found. The results obtained from synthetic peptides were in good correlation with the observed glycosylation patterns of native peptides and with the order of attachment in a multi-glycosylated peptide. The snail enzyme clearly preferred threonine over serine in the in vitro assays. No significant differences of transfer speed or efficiency could be detected using a mutant of the enzyme lacking the lectin domain. This is the first characterisation of the substrate specificity of a member of the ppGalNAcT family from mollusc origin.